Analysis of pharmaceutical assistance in SUS dispensing services in Sorriso-MT - Zampieron, R. G.; Gonçalves, D. M.; Biavatti, H. A. Z. (Scientific Electronic Archives, 2019)
This study analyzed the pharmacy assistance from Sorriso-MT through data collected in a local SUS dispensing service of medicines, as well as the attendance or not of the demand of the medicines. The method used was a descriptive, cross-sectional, descriptive exploratory study conducted from May to November 2015. Data were collected through questionnaires developed by the Ministry of Health for the National Survey on Access, Use and Promotion of Rational Use of Medicines in Brazil, the reports from the computerized system, and the prescriptions and notes. In total, 31971 recipes were obtained, with an average of 3.3 prescription drugs, with 95.8% of prescriptions being medicines listed in REMUME. The demand was 94.31%. Of the total prescriptions, 73% were made by the generic name and 17.8% contained antibiotics. It can be observed that the lack of prescription was not enough and the municipality presented a good supply of medicines, positively influencing the quality of life and rational use of medicines.